Klebsiella pneumoniae-Induced Emphysematous Prostatic Abscess Accompanied by a Spinal Cord Infarction: Case Report - Jeh, Seong Uk; Choi, Min Sung; Kang, Chang Seok; Kim, Dae Hyun; Choi, Jae Hwi; Choi, See Min; Kam, Sung Chul; Hwa, Jeong Seok; Hyun, Jae Seog (Urogenital tract infection, 2024)
Various strains can be found in emphysematous prostatic abscesses (EPAs), but the most frequent causative organism is Klebsiella pneumoniae . Hypervirulent K. pneumoniae can disseminate to distant sites by forming a muco-polysaccharide network outside the capsule. Here, we present the first case of K. pneumoniae in an EPA accompanied by a spinal cord infarction. A 65-year-old man was referred to our hospital due to sudden-onset paraplegia after a 5-day history of fever, myalgia, and voiding difficulty. Abdominal computed tomography revealed a collection of air pockets in the prostate, and diffusion-weighted magnetic resonance imaging showed high signal intensity in the thoracic spinal cord. The patient was initially treated with antibiotics and surgical drainage. On the third hospital day, therapeutic heparin was added after discussion with a neurologist. The patient had no inflammatory symptoms, experienced some improvement in paraplegia, and was discharged on the 14th hospital day. This study adhered to the case report guidelines.